2008
DOI: 10.1017/s1751731108002486
|View full text |Cite
|
Sign up to set email alerts
|

Herbage intake and behavioural adaptation of grazing dairy cows by restricting time at pasture under two feeding regimes

Abstract: The time at pasture of dairy cows is often restricted in the context of extending the grazing season in autumn or at the end of winter. The objective of our study was to evaluate the effects of a restriction of time at pasture on milk production, herbage intake and feeding behaviour in dairy cows according to feeding regime. The four treatments consisted of 4 h or 8 h of time at pasture per day tested under two feeding regimes combining rate of supplementation and herbage allowance: either a high rate of suppl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
47
1
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(59 citation statements)
references
References 21 publications
10
47
1
1
Order By: Relevance
“…In our study, a highly irregular feeding pattern distribution was deliberately chosen between treatments, herbage being fed in the morning and silage in the evening, with a widely variable amount and thus morning : evening proportions. This feeding pattern is probably close to that of dairy cows grazing during the day and supplemented indoors at night (Pé rez-Ramírez et al, 2008). It is clear that the n-alkanes method is suitable for accurately estimating herbage intake by a twice-daily faecal sampling under very different feeding patterns, type of diet and feeding level.…”
Section: Discussionsupporting
confidence: 54%
“…In our study, a highly irregular feeding pattern distribution was deliberately chosen between treatments, herbage being fed in the morning and silage in the evening, with a widely variable amount and thus morning : evening proportions. This feeding pattern is probably close to that of dairy cows grazing during the day and supplemented indoors at night (Pé rez-Ramírez et al, 2008). It is clear that the n-alkanes method is suitable for accurately estimating herbage intake by a twice-daily faecal sampling under very different feeding patterns, type of diet and feeding level.…”
Section: Discussionsupporting
confidence: 54%
“…Previous studies showed that cows were able to adjust the grazing behavior at pasture in response to PMR supplementation and/or duration of scheduled pasture allocations (Bargo et al, 2002). Cows increasingly restricted to graze at pasture generally increase the proportion of time spent grazing and/or the intake per bite, two compensatory strategies that maximize the instantaneous intake rate (Pérez-Ramírez et al, 2008;Kennedy et al, 2011). Conversely, increasing silage supplementation on same restricted cows can reduce grazing time and/or the proportion of time spent grazing (Pérez-Ramírez et al, 2008;Kennedy et al, 2011).…”
Section: Time Budgetmentioning
confidence: 99%
“…Cows increasingly restricted to graze at pasture generally increase the proportion of time spent grazing and/or the intake per bite, two compensatory strategies that maximize the instantaneous intake rate (Pérez-Ramírez et al, 2008;Kennedy et al, 2011). Conversely, increasing silage supplementation on same restricted cows can reduce grazing time and/or the proportion of time spent grazing (Pérez-Ramírez et al, 2008;Kennedy et al, 2011). Thus, cows of the present study may have adjusted the duration and/or intensity of grazing in response to PMR supplementation and available opportunities to access pasture on a voluntary basis.…”
Section: Time Budgetmentioning
confidence: 99%
“…In the autumn system, extending the grazing season through winter until the beginning of spring provides a useful means of increasing the proportion of grazed herbage in the diet of dairy cows, reducing production cost (Pérez-Ramírez et al, 2008).…”
Section: Introductionmentioning
confidence: 99%